PENGARUH PERSPEKTIF RISIKO TERHADAP UTANG LUAR NEGERI INDONESIA - Fakhruddin Fakhruddin; Ibnu Syahri Ramadhan (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
This study aims to determine the factors that influence Indonesia's foreign debt. This study are used annual data from 1980 to 2008. The model used is multiple linear regression. The results showed that no significant relationship between risk perspective and foreign debt in Indonesia. Based on the results of this study suggested the Indonesian government to keep the perspective of the risk of debt instruments abroad in Indonesia.